2016
DOI: 10.1177/1073191116665907
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality of Helicopter Parenting and Relations to Emotional, Decision-Making, and Academic Functioning in Emerging Adults

Abstract: The current study tests the underlying structure of a multidimensional construct of helicopter parenting (HP), assesses reliability of the construct, replicates past relations of HP to poor emotional functioning, and expands the literature to investigate links of HP to emerging adults' decision-making and academic functioning. A sample of 377 emerging adults (66% female; ages 17-30; 88% European American) were administered several items assessing HP as well as measures of other parenting behaviors, depression,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
101
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 49 publications
7
101
0
2
Order By: Relevance
“…These parents may engage in helicopter parenting and psychological control in order to induce continued dependency. Consistent with this argument, several studies have found overlap between parental psychological control and helicopter parenting (Luebbe et al, 2016; Padilla-Walker & Nelson, 2012). Thus, the first purpose of this study was to identify profiles of parents based on levels of helicopter parenting, parental warmth, and psychological control.…”
Section: Helicopter Parentingmentioning
confidence: 70%
See 2 more Smart Citations
“…These parents may engage in helicopter parenting and psychological control in order to induce continued dependency. Consistent with this argument, several studies have found overlap between parental psychological control and helicopter parenting (Luebbe et al, 2016; Padilla-Walker & Nelson, 2012). Thus, the first purpose of this study was to identify profiles of parents based on levels of helicopter parenting, parental warmth, and psychological control.…”
Section: Helicopter Parentingmentioning
confidence: 70%
“…Helicopter parenting is a unique form of control characterized by parents making important decisions for their child and trying to solve problems that their child could reasonably solve themselves (Hunt, 2008), such as monitoring school work or solving roommate problems (Schiffrin et al, 2014). Although there is overlap, helicopter parenting has been found to be meaningfully distinct from behavioral control and psychological control (Padilla-Walker & Nelson, 2012) and is not correlated (Nelson et al, 2015) or is negatively correlated (Luebbe et al, 2016) with parental warmth. That being said, recent research suggests that different types of helicopter parenting may exist that are paired with other aspects of parenting and may be differentially effective for children.…”
Section: Helicopter Parentingmentioning
confidence: 99%
See 1 more Smart Citation
“…Other stud ies have found that specific aspects of helicopter parenting may be associated with positive outcomes. For example, Luebbe et al (2018) reported that, when other facets of helicopter parenting (i.e., academic and personal management, direct inter ventions, and autonomylimiting behaviors) were not present, parents' informationseeking behaviors (e.g., keeping tabs on one's children and helping them make decisions) were associated with better decisionmaking and better academic functioning in college student offspring.…”
Section: Resultsmentioning
confidence: 99%
“…Posebna vrsta kontrole su ponašanja takozvanih "helikopter" roditelja (Holden, 2010). Helikopter roditeljstvo predstavlja konstelaciju roditeljskih ponašanja koja uključuju visoku angažiranost, visoku kontrolu i nisko dopuštanje autonomije djetetu u različitim kontekstima (Luebbe et al, 2016;Padilla-Walker & Nelson, 2012). Takvo ponašanje motivirano je roditeljskom brigom za dobrobit i uspjeh svoje djece, ali je neprimjereno intruzivno i upravljajuće (Padilla-Walker & Nelson, 2012) te ima negativne efekte na psihološku dobrobit odraslih u nastajanju (Segrin, Woszidlo, Givertz, & Montgomery, 2013).…”
Section: Roditeljska Kontrolaunclassified